Misconceptions of Prospective Physics Teachers in Heat Concepts: Implementation of Three-Tier Diagnostic Tests (TTDT) - Ramadhan, Teuku Muhammad Hary; Mustari, Andi; Mustika, Cut Rizki; Haya, Fadiya (Universitas Garut, 2026)
Misconceptions about heat are still very common and need further research. Misconceptions experienced by prospective physics teachers must be immediately eliminated or reduced, because if misconceptions are left unchecked, these wrong concepts can persist for a long time and affect their teaching in the future. This study aims to identify misconceptions of prospective physics teachers on the concept of heat by applying the three-tier diagnostic test (TTDT). The approach used is descriptive quantitative with a conceptual diagnostic method. The research sample consisted of 52 7th-semester students of the Physics Education Department of Syiah Kuala University who had taken basic physics and thermodynamics courses. The research instrument consisted of 30 items, consisting of 10 content items, 10 reason items, and 10 confidence level items. Student responses were grouped into three categories: Understand the Concept (PK), Misconception (M), and Don’t Understand the Concept (TPK). The results of the study showed variations in student understanding of the ten heat concepts tested. Overall, 67.7% of student responses were in the PK category, 28.3% in the M category, and 4% in the TPK category. The highest misconception was found in the concept of “Cold Objects Still Contain Heat (BDP)” and “Heat Exists in All Objects (PSB)”, which is related to misconceptions about thermal energy at the microscopic level. Meanwhile, the concept of the definition of temperature and heat, the difference between the two, and the direction of heat transfer were the most widely understood concepts. The TTDT instrument was proven in identifying detailed categories of Understand the Concept (PK), Don’t Understand the Concept (TPK), and Misconception (M).Keywords: Diagnostic, Heat Concepts, Misconceptions, Three-Tier